2016
DOI: 10.1002/elps.201600380
|View full text |Cite
|
Sign up to set email alerts
|

Performance and selectivity of cationic nanoparticle pseudo‐stationary phases in electrokinetic chromatography

Abstract: Electrokinetic chromatography (EKC) is a powerful analytical technique that uses an ionic pseudo-stationary phase (PSP) to separate neutral compounds. Although anionic surfactants are the most common choice for PSP, cationic latex nanoparticles are an attractive alternative. Reversible addition-fragmentation chain transfer (RAFT) polymerization was used to synthesize several types of diblock copolymers that self-assemble into latex nanoparticles, which were characterized by a variety of techniques including di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… also suggested that EKC could be used to characterize PSPs. Numerous materials have been developed as PSPs, and the solvent characteristics of a variety of PSP materials, including micelles , polymers ,vesicles , microemulsions , liposomes , bicelles and nanoparticles have been studied by EKC. The solvent characteristics of liposome PSPs composed of zwitterionic and anionic lipids have frequently been studied as models of lipid bilayer membranes and as a means to determine octanol water partition coefficients (P o/w ) .…”
Section: Introductionmentioning
confidence: 99%
“… also suggested that EKC could be used to characterize PSPs. Numerous materials have been developed as PSPs, and the solvent characteristics of a variety of PSP materials, including micelles , polymers ,vesicles , microemulsions , liposomes , bicelles and nanoparticles have been studied by EKC. The solvent characteristics of liposome PSPs composed of zwitterionic and anionic lipids have frequently been studied as models of lipid bilayer membranes and as a means to determine octanol water partition coefficients (P o/w ) .…”
Section: Introductionmentioning
confidence: 99%
“…The application of interest in the current study for these coatings is the separation of neutral compounds by EKC using a cationic PSP. In previous work we described the synthesis and evaluation of cationic latex nanoparticles formed from amphiphilic diblock copolymers containing a cationic block and a hydrophobic block . As presented above, these cationic nanoparticles adsorb to the capillary surface and form a cationic coating, creating an anodic EOF.…”
Section: Resultsmentioning
confidence: 99%
“…Diblock copolymer nanoparticles containing an AETMAC hydrophilic block and ethyl acrylate hydrophobic block (hereafter referred to as EAAETMAC) were synthesized in a two‐step process . AETMAC macroCTA was synthesized in the same manner as the PAETMAC capillary coating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation